2022
DOI: 10.3389/fnhum.2022.833528
|View full text |Cite
|
Sign up to set email alerts
|

The Embodiment of Architectural Experience: A Methodological Perspective on Neuro-Architecture

Abstract: People spend a large portion of their time inside built environments. Research in neuro-architecture—the neural basis of human perception of and interaction with the surrounding architecture—promises to advance our understanding of the cognitive processes underlying this common human experience and also to inspire evidence-based architectural design principles. This article examines the current state of the field and offers a path for moving closer to fulfilling this promise. The paper is structured in three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 64 publications
1
12
0
1
Order By: Relevance
“…Such an outlook on human embodiment has also sometimes been called “enactivism,” holding that interactions with the world are decisive for human experience, cognitive performance, and behavioral decisions 25,26 . For instance, research under this framework has empirically demonstrated that motor reactions are central to the ways in which humans perceive the built environment, including its shapes and geometries 27–31 …”
Section: Stimulus and Ecological Validity: An Embodied Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Such an outlook on human embodiment has also sometimes been called “enactivism,” holding that interactions with the world are decisive for human experience, cognitive performance, and behavioral decisions 25,26 . For instance, research under this framework has empirically demonstrated that motor reactions are central to the ways in which humans perceive the built environment, including its shapes and geometries 27–31 …”
Section: Stimulus and Ecological Validity: An Embodied Perspectivementioning
confidence: 99%
“…25,26 For instance, research under this framework has empirically demonstrated that motor reactions are central to the ways in which humans perceive the built environment, including its shapes and geometries. [27][28][29][30][31] If the curvature-preference effect were to be consistently identified in research settings as rich and complex as the actual built environment, then it would suggest that such responses may indeed be universal. However, the studies evaluated by Chuquichambi and colleagues 1 show a strong reliance on viewing photographs or images in a detached fashion; and in the smaller number of studies that did have more robust affordances, this curvature-preference effect could not be found.…”
Section: Stimulus and Ecological Validity: An Embodied Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies in system neuroscience and computational neuroscience, which have recently increased in number, have helped understand human sensory perception at the molecular and microcircuit levels [9][10][11][12]. An interesting new research methodology is Mobile Brain/ Body Imaging (MoBI), which records a moving person's brain activity and bodily sensations in real time [13,14]. MoBI has superior ecological validity compared to existing research methods, and since it is possible to see in real time how the brain and body react when a human is staying or moving in a specific space, it promises to be a highly useful method in the area of space and urban design.…”
Section: Introductionmentioning
confidence: 99%